2015
DOI: 10.3349/ymj.2015.56.4.1051
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Open Anterior Retroperitoneal Lumbar Interbody Fusion: Oblique Lateral Interbody Fusion for Lumbar Spinal Degeneration Disease

Abstract: PurposeSurgery for lumbar spinal degeneration disease is widely performed. While posterior decompression and fusion are popular, anterior lumbar interbody fusion (ALIF) is also used for treatment. Extreme lateral interbody fusion (XLIF) is commonly used for noninvasive ALIF; however, several complications, such as spinal nerve and psoas muscle injury, have been reported. In the current study, we examined the clinical efficacy and complications of oblique lateral interbody fusion (OLIF) for lumbar spinal degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 22 publications
2
105
0
1
Order By: Relevance
“…The lower back pain and leg pain were significantly improved. The fact that the overall parameters improved after the surgery support that efficient intervertebral fusion and correction can be achieved with OLIF surgery by using a lateral intervertebral cage followed by ligamentotaxis, which has favorable mid-term results 12,13,15,18) . It has been reported that LLIF can correct a deformity with larger lateral interbody cages.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The lower back pain and leg pain were significantly improved. The fact that the overall parameters improved after the surgery support that efficient intervertebral fusion and correction can be achieved with OLIF surgery by using a lateral intervertebral cage followed by ligamentotaxis, which has favorable mid-term results 12,13,15,18) . It has been reported that LLIF can correct a deformity with larger lateral interbody cages.…”
Section: Discussionmentioning
confidence: 78%
“…These procedures are attracting more attention since they are less invasive. Two popular and common LLIF procedures are oblique lateral interbody fusion (OLIF) and extreme lateral interbody fusion (XLIF), which each require specially designed instruments [12][13][14][15] . OLIF, especially, enables surgeons to easily and less invasively access the vacant oblique corridor in front of the psoas muscles without causing any splitting, which occurs with XLIF 16,17) .…”
Section: Introductionmentioning
confidence: 99%
“…With respect to previous studies on the oblique psoas-sparing approach, in the largest series of 179 patients, Silvestre et al [44] did not report on the general risk of infection and hematoma. Ohtori et al [36,37] used the oblique psoas-sparing approach for varying indications and only for small patient cohorts (12 and 35 patients) without reporting on either infection or hematoma. Owing to the small cohorts, these figures were not meaningful with respect to the low incidence of these complications in general.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that use of this oblique corridor, anterior to the psoas muscle, may avoid many of the anatomic structure-associated complications with the anterior or transpsoas approaches. However, studies on intra-and perioperative complications of the oblique psoassparing approach have been based on small cohorts of patients undergoing surgery for different indications [36,37,42]. Silvestre et al [44] reported the results of 179 patients who underwent oblique lumbar interbody fusion, but a single-center series focusing on inpatient complications has not been reported to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Potential complications can include vascular, bowel injuries, and sympathetic plexus, but such risk is much reduced by the ability of the surgeon of direct visualization of these structures [91,92].…”
Section: Anterior To the Psoas: Atp/olifmentioning
confidence: 99%